A violência terrorista, o direito penal do inimigo e suas implicações sobre os direitos humanos - Pádua, Gilanni Duarte Costa (2022)
The present work investigates, from a philosophical perspective, the phenomenon of terrorist violence, the Criminal Law of the Enemy, and human rights in order to understand how such phenomena can be correlated. Terrorism, as one of the cruelest forms of violence, poses numerous threats to human rights. It is a complex phenomenon and its most varied manifestations, mostly unpredictable, are overwhelming. The Criminal Law of the Enemy, in turn, developed by Günther Jakobs, assumes that certain persistent transgressors of social norms - the enemies - must be excluded from society, losing the right to have rights, and this would justify the state application of excessive penalties, suspension of legal guarantees and violation of the human rights of these enemies. This work intends to analyze if the response of the State and its agents to the terrorists, when making use of norms characteristic of the Criminal Law of the Enemy, it is legitimate, just, or if, on the contrary, it is only the expression of another violence.